Perancangan Model Pembelajaran Harga Pokok Produksi Berbasis Spreadsheet untuk Meningkatkan Pemahaman Mahasiswa - Dyah Puspitasari Sunaryo Putri; Niera Feblidiyanti (Jurnal Accounting Information System (AIMS), 2021)
Cost of Goods Manufacture Calculation is an important comprehension in the Cost Accounting course, which is a scientific discipline that has dimensions not only theoretical but also applied that cannot be separated from technological developments. Computerized practical skills are important for students. This course is not only granted to students of the Faculty of Economics, but also several study programs in other faculties and one of them is the Industrial Engineering study program. Therefore, this spreadsheet-based learning model is designed to provide practical learning process so that the students understanding of the calculation of the cost of goods manufacture can be increase. Using experimental method, the posttest scores achieved by students who received the learning method material using the spreadsheet program was significantly different with students who did not receive the spreadsheet program material. The conclusion is that the learning model using a spreadsheet was able to effectively improve students' understanding of the material for calculating the cost of manufacture.